Vicinal land use change strongly drives stream bacterial community in a tropical montane catchment - Le, Huong T; Rochelle-Newall, Emma; Auda, Yves; Ribolzi, Olivier; Sengtaheuanghoung, Oloth; Thébault, Elisa; Soulileuth, Bounsamay; Pommier, Thomas (FEMS microbiology ecology, 2018)
Impact of land use (LU) change on stream environmental conditions and the inhabiting bacterial community remains rarely investigated, especially in tropical montane catchments. We examined the effects of LU change and its legacy along a tropical stream by comparing seasonal patterns of dissolved organic carbon (DOC) / colored dissolved organic matter (CDOM) in relation to variations in structure, diversity and metabolic capacities of particle-attached (PA) and free-living (FL) bacterial communities. We hypothesized that despite seasonal differences, hydrological flows that accumulate allochthonous carbon along the catchment are a major controlling factor of the bacterial community. Surprisingly, local environmental conditions that were largely related to nearby LU and the legacy of LU change were more important for stream bacterial diversity than hydrological connectivity. DOC was strongly correlated with PA richness and diversity. The legacy of LU change between teak plantation and annual crops induced high DOC and high diversity and richness of PA in the adjacent waters, while banana plantations were associated with high diversity of FL. The community structures of both PA and FL differed significantly between seasons. Our results highlight the importance of vicinal LU change and its legacy on aquatic bacterial communities in mixed used tropical watersheds.